Pious ambitions Sally Merriam Wait's mission south, 1813-1831 - Tribble, Mary C. (Knoxville The University of Tennessee Press, 2021)
"Mary C. Tribble mines a journal and a trove of letters from the Special Collections and Archives of Z. Smith Reynolds Library at Wake Forest University to introduce a significant figure in North Carolina and Baptist history. The writings of Sally Merriam Wait reveal a northernborn woman with anti-slavery leanings engaging with an unfamiliar environment in the slave-holding South. Her ambition led her from young convert in revival-swept New England to devoted wife of Reverend Samuel Wait, the first president and founder of Wake Forest University. Wait's decisions are shaped by a surging evangelical movement, changes in the American economy, the rise of women's social agency, a fracturing of political traditions, and the moral conflicts inherent in a slave economy. The book provides a rare glimpse into the spiritual and worldly education of a young woman of faith at the dawn of market capitalism in Jacksonian America"--
Includes bibliographical references and index
Keywords: Wait, Sarah Merriam -- 1794-1871; Spouses of clergy -- North Carolina -- Biography; Baptists -- North Carolina -- Biography; Baptists -- Missions -- North Carolina; North Carolina -- Church history -- 19th century